Identification and Counting of Bacterial Colonies on Mobile Phones Before and After 70% Alcohol Disinfection - Hutabarat, Mustika Sari; Sinaga, Hotman (Universitas PGRI Palembang, 2023)
Cell phones have become a very important communication tool in everyday life. Considering that many people are in the habit of using their mobile phones while doing other activities, most people even have the habit of taking their phones to the toilet. Cell phones become inanimate objects that play an important role in the transmission of microorganisms. Therefore, we need to maintain hand hygiene by keeping our hands clean after handling the mobile phone before performing activities and disinfecting the mobile phone regularly, considering that this object cannot be washed while the mobile phone is a potential vector for infectious diseases. Mobile phones can effectively eliminate hand hygiene due to their compulsive use despite hand washing. The purpose of this study was to determine the role of 70% alcohol cotton on the surface of mobile phones to reduce the potential spread of bacteria. Based on the results of the research conducted, there is a difference in the number of bacterial colonies on mobile phones before and after disinfection with 70% alcohol cotton, as evidenced by the obtained p-value of 0.0001 (p <0.05).